A novel strategy to achieve effective drug delivery: exploit cells as carrier combined with nanoparticles - Liang Pang; Chun Zhang; Jing Qin; Limei Han; Ruixiang Li; Chao Hong; Huining He; Jianxin Wang (Taylor & Francis Group, 2017)
Cell-mediated drug delivery systems employ specific cells as drug vehicles to deliver drugs to targeted sites. Therapeutics or imaging agents are loaded into these cells and then released in diseased sites. These specific cells mainly include red blood cells, leukocytes, stem cells and so on. The cell acts as a Trojan horse to transfer the drug from circulating blood to the diseased tissue. In such a system, these cells keep their original properties, which allow them to mimic the migration behavior of specific cells to carry drug to the targeted site after in vivo administration. This strategy elegantly combines the advantages of both carriers, i.e. the adjustability of nanoparticles (NPs) and the natural functions of active cells, which therefore provides a new perspective to challenge current obstacles in drug delivery. This review will describe a fundamental understanding of these cell-based drug delivery systems, and discuss the great potential of combinational application of cell carrier and NPs.